Paving the way for large-scale micropropagation of Juglans 3 intermedia using genetically identified hybrid seed - Phạm, Ngọc Tuân (Springer Science+Business Media Dordrecht, 2022)
This study provides a basic tool for the production of a multiclonal variety of Juglans nigra 9 J. regia hybrids (J. 9 intermedia), including optimized in vitro propagation methods and DNA-based techniques for the identification of hybrid seeds. Following identification of hybrid seed material using DNA markers embryo axes dissected from mature nuts were used as primary explants for establishing shoot cultures. The growth of shoot cultures of four hybrid genotypes was compared on two different basal media (Rugini and DKW) with three concentrations (2.2; 4.4; and 8.8 lM) of 6-benzylaminopurine (BA), and three gelling agents (Oxoid agar, Kobe agar, Gelrite). Three indole-3-butyric acid (IBA) concentrations (4, 12, and 20 lM) were compared for root induction, as well as three media for root expression. In general, the best combination of shoot elongation and production of new axillary shoots was achieved with 4.4 lM BA and 0.2 lM IBA in Rugini and in DKW medium. However, shoot elongation in most genotypes was favored when 2.2 lM BA and 0.2 lM IBA was used, in both, DKW and Rugini medium. The optimal gelling agent for Juglans hybrid shoot cultures was Kobe agar in Rugini medium. Highest rooting percentages were obtained on DKW medium with 12 lM IBA with 5 days in darkness followed by root expression under light on a mixture of gelified DKW medium and vermiculite. During acclimatization, more than 75 % of the plantlets continued to grow vigorously.